Cantrell Syndrome—A Rare Complex Congenital Anomaly: A Case Report and Literature Review - Mărginean, Claudiu; Mărginean, Cristina Oana; Gozar, Liliana; Meliţ, Lorena Elena; Suciu, Horaţiu; Gozar, Horea; Crişan, Andrada; Cucerea, Manuela (Frontiers in Pediatrics, 2018)
Cantrell syndrome (CS) or pentalogy of Cantrell is defined as a rare condition involving a midline anterior abdominal wall defect, a distal sternal cleft, a defect of the anterior diaphragm, and a defect of the apical pericardium with pericardio-peritoneal communication, as well as intracardiac anomalies. We report the case of a male newborn with type 2 CS diagnosed during intrauterine life based on ultrasonographic evaluation. Clinical examination at birth revealed an abdominal wall defect with extrathoracic displacement of the heart and a diastasis of the sagittal suture. Postnatal echocardiography revealed tricuspid atresia, partial extrathoracic and extra-abdominal displacement of the heart and liver, a large ventricular septal defect, severe subpulmonary stenosis, hypoplasia of the pulmonary artery, and a large hourglass-shaped left ventricle secondary to narrowing of the heart at the level of its extrathoracic displacement. Computed tomography showed additional abnormalities including increased left ventricular volume with extrathoracic apical aneurysmal dilatation below the xiphoid process at the level of anterior abdominal wall, a hypoplastic right ventricle, partial transparietal herniation of the left hepatic lobe adjacent to a left ventricular diverticulum, and an adrenal hematoma. The newborn received intensive medical management during his first week of life; however, surgical management had to be postponed owing to his unstable condition. Eventually, it was performed on the 14th day of life, but unfortunately, the newborn died shortly after the procedure.